The Intellectual Structure of Social Media Marketing Research: A Bibliometric Analysis and Future Research Agenda - Shahri Abu Seman (Har Press Indonesia, 2026)
The rapid growth of digital technologies and online platforms has significantly transformed marketing practices, leading to the increasing importance of social media marketing in contemporary business strategies. As scholarly interest in this field continues to expand, it becomes essential to understand the intellectual structure and thematic development of social media marketing research. This study aims to map the knowledge structure and identify key research themes within the social media marketing literature through a bibliometric analysis. Using data retrieved from the Scopus database, this research applies bibliographic coupling and network visualization techniques with the assistance of VOSviewer to analyze relationships among publications and identify major thematic clusters within the field. The findings reveal several interconnected research streams that highlight the role of social media in shaping digital marketing strategies, consumer engagement, brand relationships, and consumer decision-making processes. The results also demonstrate that social media marketing research is inherently multidisciplinary, integrating perspectives from marketing, digital communication, and business management. By mapping the intellectual structure of the field, this study contributes to a deeper understanding of the evolution of social media marketing research and provides a foundation for identifying emerging research directions and future research opportunities in digital marketing.